1987
DOI: 10.1177/088626058700200404
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sexual Abuse on Children

Abstract: Data were collected at the Sexual Assault Center in Seattle on 369 sexually abused children and a community comparison sample of 318 not-abused children. Data describing the behavior of these children were collected from the child's parent and for the abused children from the social worker. Samples differed on a number of variables and these variables were used as control variables in the analysis. Results indicate that abused and not-abused children appear behaviorally different on a set of factors and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 9 publications
2
55
0
1
Order By: Relevance
“…Additionally, it was the dysfunctional environment, rather than the abusive experience itself, that was hypothesized, but not investigated, by some of the authors reviewed (i.e., Clausen & Crittenden, 1991 as cited in Kendall-Tackett et al, 1993) to produce the trauma and symptomatology following CSA, while other authors (i.e., Conte & Schuerman, 1987) have research evidence that the environment plays a large role in the way an abusive experience contributes to the child's symptomatology. In general, it is suggested that outcomes are related to the abuse experience and how that experience interacts with the family environment and the response of others to the abuse, with victims in a family with little dysfunction and adequate support having better recovery than those in families with much dysfunction and little support (Kendall-Tackett et al, 1993).…”
Section: Family Stress (Economic and Relational)mentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it was the dysfunctional environment, rather than the abusive experience itself, that was hypothesized, but not investigated, by some of the authors reviewed (i.e., Clausen & Crittenden, 1991 as cited in Kendall-Tackett et al, 1993) to produce the trauma and symptomatology following CSA, while other authors (i.e., Conte & Schuerman, 1987) have research evidence that the environment plays a large role in the way an abusive experience contributes to the child's symptomatology. In general, it is suggested that outcomes are related to the abuse experience and how that experience interacts with the family environment and the response of others to the abuse, with victims in a family with little dysfunction and adequate support having better recovery than those in families with much dysfunction and little support (Kendall-Tackett et al, 1993).…”
Section: Family Stress (Economic and Relational)mentioning
confidence: 99%
“…Multifaceted models of traumatization have been proposed by researchers (Conte & Schuerman, 1987;Finkelhor & Browne, 1985;Kendall-Tackett et al, 1993) as an explanation for outcomes following CSA. Specifically, Finkelhor and Browne (1985) hypothesize that there are four components to the trauma that a victim experiences following CSA: powerlessness, traumatization related to early sexualization, stigmatization, and betrayal.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There is consistent evidence that familial responses and social support following the initial disclosure of abuse serve to aggravate or mitigate the trauma experienced by children (Conte & Schuerman, 1987;Everson, Hunter, Runyon, Edelsohn, & Coulter, 1989;Gomes-Schwartz, Horowitz, & Cardarelli, 1990). As important as these immediate interactions appear to be, the potential for long-term interpersonal functioning to hinder or promote the psychological wellbeing and recovery of adult survivors is largely unknown.…”
Section: Future Research Directionsmentioning
confidence: 99%